MANAGING COMMUNICATION PROCESS IN THE ORGANIZATIONAL CHANGES: The Case of PT XYZ - Masyhuri, Muhammad (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
Communication is vital to the effective implementation of organizational changes. During the major organizational changes within the organization, a good and suitable communication process is needed and important to improve company’s operation performance.  The aim of this paper is to analyze communication problems during organizational changes and to propose the appropriate interventions in the organization’s case study. Three major internal communication barriers are found and indicated which related to the geography, culture and people problems.  Through applying not only ICT’s approaches, but also implementing training, education and workshop as well as boundary spanners programs, those communication problems could be overcame. To cite this article (7th APA style): Masyhuri, M.. (2019). Managing Communication Process in the Organizational Changes: The Case of PT XYZ. Journal Communication Spectrum, 9(1), 42-56. http://dx.doi.org/10.36782/jcs.v9i1.116